Gene expansion in the hawkmoth Manduca sexta drives evolution of food-associated odorant receptors - Megha Treesa Tom; Philipp Brand; Sascha Bucks; Jin Zhang; Mario Ernesto Escobar Huezo; Bill S. Hansson; Sonja Bisch-Knaden (iScience)
Summary: In insects, odorant receptors (ORs) are required for the detection of most olfactory cues. We investigated the function of a clade of four duplicated ORs in the hawkmoth Manduca sexta and found that these paralogs encode broadly tuned receptors with overlapping but distinct response spectra. Two paralogs, which arose after divergence from a related lineage, show high sensitivity to floral esters released by a nectar-rich plant frequently visited by M. sexta. Functional imaging in mutant moths lacking one of the paralogs suggests that olfactory sensory neurons expressing this OR target a previously identified feeding-associated glomerulus in the primary olfactory center of the brain. However, only the response of this glomerulus to the single ligand unique to the now mutated OR disappeared, suggesting neuronal coexpression of the paralogs. Our results suggest a link between the studied OR expansion and enhanced detection of odors emitted by valuable nectar sources in M. sexta.